2020
DOI: 10.1038/s41467-020-16673-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutational bias and the protein code shape the evolution of splicing enhancers

Abstract: Exonic splicing enhancers (ESEs) are enriched in exons relative to introns and bind splicing activators. This study considers a fundamental question of co-evolution: How did ESE motifs become enriched in exons prior to the evolution of ESE recognition? We hypothesize that the high exon to intron motif ratios necessary for ESE function were created by mutational bias coupled with purifying selection on the protein code. These two forces retain certain coding motifs in exons while passively depleting them from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Our result confirms the prediction that purifying selection generally restricts the ability of sequence to evolve to a lower mutability state. A similar pattern was simulated by Rong et al (2020) when modeling the evolution of splice sites. The fact that coding sequence had higher mutability was not solely driven by the highly mutable CpG trinucleotides as simulations removing CpG trinucleotides produced a qualitatively similar result.…”
Section: Resultssupporting
confidence: 54%
“…Our result confirms the prediction that purifying selection generally restricts the ability of sequence to evolve to a lower mutability state. A similar pattern was simulated by Rong et al (2020) when modeling the evolution of splice sites. The fact that coding sequence had higher mutability was not solely driven by the highly mutable CpG trinucleotides as simulations removing CpG trinucleotides produced a qualitatively similar result.…”
Section: Resultssupporting
confidence: 54%
“…It is conceivable that once the pyrimidine content in the 3PT increased due to avoidance of the 3’ splice signal, splicing factors co-evolved with this pattern to develop higher binding specificity to pyrimidines. In a similar manner, it has also recently been shown that mutation bias together with purifying selection created precursor exonic splicing enhancers (pre-ESEs), to which trans-acting factors adapted later (Rong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, prior analyses ( 55 ) detected no evidence for selection operating on the candidate ( 110 ) ESS motifs when in exons. The motifs also don’t show avoidance of stop codons, despite CDS exonic motifs being motifs that should (by definition) have low stop codon density ( 40 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…ESEs may also exist in a sequence space that is especially prone to disruptive nonsense mutations. Despite the purine enrichment of both ESEs and stop codons, ESEs have a low density of TAA, TGA and TAG motifs ( 40 ) (see also 50 ). This may well reflect the fact that, while such motifs need only avoid nonsense mutations in one frame, they tend to be employed in all frames ( 51 ).…”
Section: Introductionmentioning
confidence: 99%